Research progress on brain network imaging biomarkers of subjective cognitive decline - Han Yingmei; Wang Chaojie; Zhang Yi; Li Yijie; Zhang Heng; Feng Ze; Li Weiqing; Chu Bingyuan; Wang Feng (Frontiers in Neuroscience)
PurposeSubjective cognitive decline (SCD) is an early manifestation of the Alzheimer’s disease (AD) continuum, and accurately diagnosing SCD to differentiate it from neurotypical aging in older adults is a common challenge for researchers.MethodsThis review examines and summarizes relevant studies regarding the neuroimaging of the AD continuum, and comprehensively summarizes and outlines the SCD clinical features characterizing along with the corresponding neuroimaging changes involving structural, functional, and metabolic networks.ResultsThe clinical characteristics of SCD include a subjective decline in self-perceived cognitive function, and there are significant imaging changes, such as reductions in gray matter volume in certain brain regions, abnormalities in the integrity of white matter tracts and diffusion metrics, alterations in functional connectivity between different sub-networks or within networks, as well as abnormalities in brain metabolic networks and cerebral blood flow perfusion.ConclusionThe 147 referenced studies in this paper indicate that exploring the structural, functional, and metabolic network changes in the brain related to SCD through neuroimaging aims to enhance the goals and mission of brain science development programs: “Understanding the Brain,” “Protecting the Brain,” and “Creating the Brain,” thereby strengthening researchers’ investigation into the mechanisms of brain function. Early diagnosis of SCD, along with prompt intervention, can reduce the incidence of AD spectrum while improving patients’ quality of life, even integrating numerous scientific research achievements into unified and established standards and applying them in clinical practice by doctors, thus all encouraging researchers to further investigate SCD issues in older adults.